O objeto autístico e sua função no tratamento psicanalítico do autismo - Paula Ramos Pimenta (2012)
This thesis focuses on investigating the autistic object and its participation in the psychoanalytic treatment of autistic children. The methodology used is the Case Study, evoking clinic practice to raise a question which is answered theoretically. The research field is composed of the author's clinic, which serves children and adolescents with autism since 1996, and cases of psychoanalytic literature and other. The paper begins by the nosological description of Autism, marking the absence of social interaction as the core of its diagnosis. In contrast, the good relationship with objects indicates that they occupy a strategic place in the treatment. The autistic objects were considered by some authors as harmful to social interaction of autistic patients and deemed to be alienating instruments. The French psychoanalyst Jean-Claude Maleval notes the dynamic characteristics to differentiate such objects into two categories: simple and complex. The complex autistic objects promote the possibility of a social bond for autistic patients. The simple autistic objects serve as support for the double feature, which is a typical autistic defense. To investigate the special place reached by objects, one explores the body constitution of the subject, pointing out that, in autism, it did not happen. The particularity of language in autism is investigated, concluding that there was no subtraction of the object voice. A case described in literature is used to determine the importance of the double feature and the objects to conduct the proposed treatment. We conclude by considering the relevance of the institution for the treatment of these children.